2022
DOI: 10.1002/jtr.2560
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relevance of Social Exchange Theory in the Middle East: A case study of tourism in Dubai, UAE

Abstract: Whilst numerous studies have explored residents' perceptions of tourism, there are three significant gaps with Social Exchange Theory (SET). First, the appropriateness and generalisability; second, the heterogeneity of host population perceptions; third, perceptions in non-Western empirical contexts. A mixed methods study was conducted, using 36 face-to-face interviews with expatriates and nationals in Dubai to develop a survey instrument which returned over 400 responses. Results show that whilst SET is appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
2
5
0
Order By: Relevance
“…The economic, social and cultural effects are considered as largely positive, with these results concurring with evidence of similar studies (Kowalik, 2012;Bathelt et al, 2014). Specifically for the economic benefits, the literature has showed that they are closely related to residents' support for tourism (Dutt et al, 2022), a research finding that was also highlighted in this study. By contrast, in the environmental field, the citizens of Thessaloniki consider the negative impacts, such as traffic congestion, noise, air pollution and car parking issues, as relatively insignificant.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The economic, social and cultural effects are considered as largely positive, with these results concurring with evidence of similar studies (Kowalik, 2012;Bathelt et al, 2014). Specifically for the economic benefits, the literature has showed that they are closely related to residents' support for tourism (Dutt et al, 2022), a research finding that was also highlighted in this study. By contrast, in the environmental field, the citizens of Thessaloniki consider the negative impacts, such as traffic congestion, noise, air pollution and car parking issues, as relatively insignificant.…”
Section: Discussionsupporting
confidence: 92%
“…The economic, social and cultural effects are considered as largely positive, with these results concurring with evidence of similar studies (Kowalik, 2012; Bathelt et al , 2014). Specifically for the economic benefits, the literature has showed that they are closely related to residents' support for tourism (Dutt et al , 2022), a research finding that was also highlighted in this study.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The Gulf countries, and especially the UAE, offer an interesting location to explore career development in tourism. Dubai, one of the seven emirates of the UAE, is probably one of the more well-known global tourism destinations where tourism plays a significant role in the economy (Dutt et al , 2022). The nature of employment in the UAE, and the Gulf at large, also possess noteworthy characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chiefly, the large expatriate population (Newnham and Dutt, 2022a; Wilson and Dutt, 2022) and the difficulty, in some cases the impossibility, to receive permanent citizenship (Newnham and Dutt, 2022a). While exact statistics are unclear, it is estimated that approximately 90% of the UAE’s population are expatriates (Dutt et al , 2022). The size and renown of the tourism industry coupled with the country’s familiarity with hosting expatriates makes it a very appealing destination for young people to live, start and grow their career (Wilson and Dutt, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%